E-Government and Digital Participation: Acehnese Perceptions of Digital Public Service Applications (Open Society Conference, 2025)
Accelerating digital-based bureaucratic transformation has been a strategic program of the Indonesian government since the enactment of Law No. 95 of 2018 concerning Electronic-Based Government Systems and strengthened through Presidential Regulation No. 82 of 2023. Aceh faces unique challenges due to its special autonomy status and the implementation of Islamic law, requiring it to adopt national innovations in digitalizing public administration amidst gaps in ICT infrastructure and socio-cultural characteristics that could potentially impact public participation. This study focuses on analyzing Acehnese people's perceptions of digital public service applications as a form of e-Government implementation, considering aspects of convenience, trust, and digital participation. The objective is to measure the level of acceptance, utilization, and public engagement, while identifying barriers to providing recommendations for improving inclusive services. Data are sourced from journals, official government websites, laws and regulations, and online news. The analysis was conducted using NVivo 12 Plus through the Crosstab feature, with the main theory being Davis's (1989) Technology Acceptance Model (TAM). The results show that the utilization of digital public services in Aceh is uneven and tends to fluctuate over the past four years. Services such as e-JKN and Samsat Online have seen improvements, while e-passports and population administration remain low. This finding reinforces the TAM framework, which states that perceived usefulness and ease of use determine technology adoption, while structural barriers such as limited infrastructure, digital literacy, and minimal policy dissemination hinder participation. Improving service quality requires strengthening infrastructure, simplifying interfaces, and effective public communication.